KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM DALAM PENILAIAN AUTENTIK DI SMA NEGERI 1 ARGA MAKMUR - sulistiati sulistiati (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2019)
Abstact: This research was motivated by the fact that many teachers of Islamic education and manners have not implemented authentic assessment as a whole, whereas the authentic assessment is a requirement of the implementation of the curriculum in 2013.This study aims to answer the problem:1) How is the competence of teachers PAI in designing authentic assessment in religious education and Courtesy of SMA Negeri 1 Arga Makmur? 2) How is the competence of teachers PAI in implementing authentic assessment in religious education and Courtesy of SMA Negeri 1 Arga Makmur? 3) How PAI teacher competence in managing authentic assessment in Islamic education and Budi Character in SMA Negeri 1 Arga Makmur? 4) What are the factors supporting and inhibiting the success of authentic assessment in SMA N 1 Arga Makmur?.Who became informants in this study were teachers PAI SMA N 1 Arga Makmur. This type of research is qualitative descriptive. Data collection techniques used include: interviews, observation, and documentation. Data analysis methods used there are three stages of data reduction, data presentation, and conclusion. Based on research carried out showed that: Effectiveness of competence of teachers of Islamic religious education in authentic assessment are:in terms of planning, teachers are designing and preparing authentic assessment process in accordance with the principles of curriculum assessment in 2013.In terms of implementation, authentic assessment carried out by the Islamic religious education teachers and manners adapted to the material being taught, so that the whole is not authentic assessment process that can be implemented as a whole in the learning process of Islamic religious education and moral.In terms of management, authentic assessment has been carried out properly as documented in the form of report cards and assessment records.Factor that into a successful process of authentic assessment in the form of readiness of teachers in the assessment process that is followed by the 2013 curriculum training and mentoring of teachers of principals and supervisors. Factors inhibiting the adjustment between the types of assessments to the characteristics of students of students, so that the assessment process can not reach KKM.